1999
DOI: 10.1103/physrevb.60.3899
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure ofiAl68Pd23Mn

Abstract: A Fibonacci-like terrace structure along a fivefold axis of i-Al 68 Pd 23 Mn 9 monograins has been observed by Schaub et al. with scanning tunneling microscopy. In the planes of the terraces they see patterns of dark pentagonal holes. These holes are well oriented both within and among terraces. In one of 11 planes Schaub et al. obtain the autocorrelation function of the hole pattern. We interpret these experimental findings in terms of the T * (2F) tiling decorated by Bergman and Mackay polytopes. Following t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 12 publications
5
47
0
Order By: Relevance
“…21 Recently, Papadopolos et al have compared the characteristic distances measured by Schaub et al with arrangements of the Bergman clusters beneath one particular plane. 18,19 The characteristic distances separating Bergman clusters buried beneath this particular plane are shown by the values in brackets in the middle column of Table I. They were calculated from an exact geometrical construction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recently, Papadopolos et al have compared the characteristic distances measured by Schaub et al with arrangements of the Bergman clusters beneath one particular plane. 18,19 The characteristic distances separating Bergman clusters buried beneath this particular plane are shown by the values in brackets in the middle column of Table I. They were calculated from an exact geometrical construction.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It has been suggested that these represent specific types of atoms in the surface, e.g., Mn surrounded by Al-Pd pentagons. 17 It has also been suggested 18,19 that these may represent parts of the Bergman cluster, which is a structural unit emphasized in other structural models. 20,21 The present paper elucidates the discussion of the terrace fine structure.…”
Section: Introductionmentioning
confidence: 99%
“…3 The surface structure of this material has been identified and determined to be a termination of the bulk structure. [4][5][6][7][8][9][10][11][12] The local atomic configuration ͓see Fig. 1͑a͔͒ is best described with pentagonal dark stars, pentagons and flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Let us briefly recall how the Bergman clusters are used to decorate the tiling T * (2F) [10,14]. In a first step, from the the tiling T * (2F) we locally derive the primitive or Amman-Kramer tiling T (P) .…”
mentioning
confidence: 99%